Protein kinase Cβ as a therapeutic target stabilizing blood-brain barrier disruption in experimental autoimmune encephalomyelitis - Lanz, Tobias; Becker, Simon; Osswald, Matthias; Bittner, Stefan; Schuhmann, Michael K.; Opitz, Christiane; Gaikwad, Sadanand; Wiestler, Benedikt; Litzenburger, Ulrike; Sahm, Felix; Ott, Martina; Iwantscheff, Simeon Alexander; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Disruption of the blood-brain barrier (BBB) is a hallmark of acute inflammatory lesions in multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis. This disruption may precede and facilitate the infiltration of encephalitogenic T cells. The signaling events that lead to this BBB disruption are incompletely understood but appear to involve dysregulation of tight-junction proteins such as claudins. Pharmacological interventions aiming at stabilizing the BBB in MS might have therapeutic potential. Here, we show that the orally available small molecule LY-317615, a synthetic bisindolylmaleimide and inhibitor of protein kinase Cβ, which is clinically under investigation for the treatment of cancer, suppresses the transmigration of activated T cells through an inflamed endothelial cell barrier, where it leads to the induction of the tight-junction molecules zona occludens-1, claudin 3, and claudin 5 and other pathways critically involved in transendothelial leukocyte migration. Treatment of mice with ongoing experimental autoimmune encephalomyelitis with LY-317615 ameliorates inflammation, demyelination, axonal damage, and clinical symptoms. Although LY-317615 dose-dependently suppresses T-cell proliferation and cytokine production independent of antigen specificity, its therapeutic effect is abrogated in a mouse model requiring pertussis toxin. This abrogation indicates that the anti-inflammatory and clinical efficacy is mainly mediated by stabilization of the BBB, thus suppressing the transmigration of encephalitogenic T cells. Collectively, our data suggest the involvement of endothelial protein kinase Cβ in stabilizing the BBB in autoimmune neuroinflammation and imply a therapeutic potential of BBB-targeting agents such as LY-317615 as therapeutic approaches for MS.